Community Assistance in the Implementation of Disaster-Resilient Village Strengthening Policies in Perk. Bukit Lawang Village - Istiawati, Sri; Elisa, Nufaris; Fachrudin, Khaira Rizfia; Siregar, Yulkarnaini (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This study was conducted to describe community assistance in the implementation of the Disaster-Resilient Village policy in Perk. Bukit Lawang Village. The research method used in this study is descriptive analysis with a qualitative approach. The theoretical framework explains that policy implementation is influenced by communication, resources, disposition, and bureaucratic structure. Data collection techniques include literature studies, observation, interviews, and documentation. The results of this study indicate that the implementation of the Disaster-Resilient Village policy in Perk. Bukit Lawang Village has not been optimal. In the communication dimension, the dissemination of information by the Perk. Bukit Lawang Village Government has been insufficient. There are also shortcomings in the resource dimension, including an inadequate number of human resources and limited budgetary resources, resulting in insufficient facilities and infrastructure. The disposition, or the ability of implementers to respond to problems, has been responsive. Meanwhile, the bureaucratic structure applies Standard Operating Procedures in the implementation of activities.